Molecular characterisation of novel reassortants of the G57 genotype of low-pathogenic avian influenza H9N2 virus isolated from poultry farms in Malaysia - Gunasekara, Erandi; Hair-Bejo, M.; Aini, I.; Omar, A. R. (Springer, 2024)
In late 2017, Malaysia reported repeated outbreaks of low-pathogenic avian influenza virus (LPAI) H9N2 infections in commercial poultry flocks. Two H9N2 viruses, A/chicken/Malaysia/Negeri Sembilan/UPM994/2018 and A/chicken/Malaysia/Johore/UPM2033/2019, which were isolated from breeder and layer flocks in Peninsular Malaysia, were characterised in this study. Phylogenetic analysis revealed that both viruses were multiple-genotype reassortant strains with genes originating from Y280-like (HA gene), F/98-like (NS, NP and PA), G1-like (M and PB2), and Korean-like (PB1) lineages, indicating that they belong to a novel genotype that is divergent from the G57 lineage of Chinese origin. Both isolates were predicted to have a dibasic cleavage site (333-PSRSSRGLF-341) in the HA gene cleavage locations. Thus, the novel Malaysian H9N2 strain is a Y280-like virus resembling H9N2 isolates from Indonesia, Taiwan, Japan, and Cambodia. This virus is of the G57 lineage but has a novel genotype of the PB1 gene originating from a Korean-lineage H9N2 virus, which has not been detected before in the region.